Pola Komunikasi “Shihab & Shihab” pada Narasi TV dalam Perspektif Etnografi Komunikasi - Fahmi Gunawan; NFN Abbas (Balai Bahasa Provinsi Riau, 2019)
This study aims to examine the communication patterns of “Shihab & Shihab” on Narasi TV with the episode of